Iphigenia's sacrifice: generational historicity as a structure of feeling in times of austerity. (14th October 2020) - Theodossopoulos, Dimitrios
Abstract: Iphi, an unemployed actor in austerity‐ridden Greece, imagines a theatre adaptation of a classic tragedy, Iphigenia at Aulis, in which the heroine is sacrificed on the altar of austerity by politicians. While writing her playscript, Iphi has a dream: she is taken to the sacrificial altar, not by politicians, but by her own parents, the generation who lived through the affluent years before austerity. Iphi's generational‐analogical thinking introduces a politically inspiring historicity, which offers insights into the accountability of austerity. It also allows us to reassess the notion of generations as a local category and an anthropological analytical construct. The article indicates the emergence of an as yet not fully articulated generational awareness – a new structure of feeling – about austerity, which is outlined here as it develops in an incipient form. I argue that the emerging generational historicity communicates a critical message, but also hides from view less visible inequalities. Abstrait: Le sacrifice d'Iphigénie : l'historicité générationnelle comme structure du sentiment à l'heure de l'austérité Résumé Iphi, actrice au chômage dans une Grèce rongée par l'austérité, imagine une adaptation théâtrale d'une tragédie classique, Iphigénie à Aulis, dans laquelle l'héroïne est sacrifiée sur l'autel de l'austérité par les politiciens. Alors qu'elle écrit son script, Iphi fait un rêve : c'est elle qui est mise sur l'autel sacrificiel, et pas par les politiciens mais par ses propres parents, la génération qui a connu les années d'abondance avant l'austérité. La pensée analogico‐générationnelle d'Iphi présente une historicité politiquement inspirante qui explore la responsabilité de l'austérité. Elle invite également à revoir la notion de générations en tant que catégories locales et constructions analytiques anthropologiques. Cet article évoque l'émergence d'une conscience générationnelle pas encore pleinement exprimée – une nouvelle structure du sentiment – autour de l'austérité, et résumée ici dans ses balbutiements. L'auteur avance que cette historicité générationnelle émergente émet un message critique, mais dissimule également des inégalités moins visibles.